2021
DOI: 10.3389/fpsyg.2021.620739
|View full text |Cite
|
Sign up to set email alerts
|

Centennials, FOMO, and Loneliness: An Investigation of the Impact of Social Networking and Messaging/VoIP Apps Usage During the Initial Stage of the Coronavirus Pandemic

Abstract: The current COVID-19 pandemic has had obvious, well-documented devastating effects on people's physical health. In this research, we investigate its potential effects on people's mental health. Many people have experienced social isolation, as countries attempt to stem the spread of the disease through confinement and other forms of social distancing. Intuitively, such social isolation may increase feelings of loneliness, and people may take logical steps to reduce their feelings of social isolation and loneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 69 publications
(61 reference statements)
6
47
0
3
Order By: Relevance
“…Few were conducted in Oceania ( n = 3), America ( n = 2), and Middle East ( n = 1). One study ( 36 ) collected data from Italy, Argentina, and United Kingdom. Six studies adopted a longitudinal design, ranging from 14 days ( 37 ) to twelve months ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Few were conducted in Oceania ( n = 3), America ( n = 2), and Middle East ( n = 1). One study ( 36 ) collected data from Italy, Argentina, and United Kingdom. Six studies adopted a longitudinal design, ranging from 14 days ( 37 ) to twelve months ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies reported that social media use increased during the Covid-19 pandemic ( 36 , 47 , 56 , 60 , 62 ), including the usage of a variety of social media platforms (e.g., Instagram, Snapchat, TikTok). In particular, three studies reported that about one-third of the participants used social media for more than 5 h per day ( 40 , 50 , 56 ), with some participants reporting time spent on social platforms up to 10 h per day ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of digital communication technologies is therefore not entirely foreign to older people, and researchers suggest that these technologies have beneficial effects on the everyday functioning of older adults. Studies suggest that use of digital communication technologies, as well as the use of social media networks, may potentially mitigate increased loneliness following forced social isolation (Fumagalli et al, 2021). Older adults who use video call apps (such as Skype) are estimated to show a twofold decrease in depressive symptoms; however, depression rates among older people using instant messaging and social media networks were similar to those who did not use any communication technology (Teo, Markwardt, & Hinton, 2019).…”
Section: Maintaining Relationships During the Covid-19 Pandemicmentioning
confidence: 99%